MAPPING OF LANGUAGES IN TIMOR TENGAH SELATAN REGENCY - Jeladu Kosmas; Fransikus Sanda; Alex Djawa; Fransiskus Bustan (Postgraduate School, Universitas Nusa Cendana, 2020)
The research about dialect mapping in Timor Tengah Selatan regency is one of the forms of the effort in expressing the truth of humanities researchers who have exposed the Dawan language on the map of languages ​​in East Nusa Tenggara. The researcher wants to minimize the doubts of Lauder (1997) who stated that if all linguistic and non-linguistic researchers agree to use research methods and criteria in selecting the same languages, dialects, sub-dialects, and variants, It is probable that the gap between the findings of one researcher and another can be minimized. Thus, this study specifically wants to map the languages, dialects, sub-dialects, and variants that are in TTS regency. The object of this research is targeting the portrait of the Dawan language map which contains languages, dialects, sub-dialects, and variants derived in the Timor Tengah Selatan Regency, East Nusa Tenggara Province. This study uses dialectometric techniques which are often used in diachronic linguistics. The findings of this study were (1) finding a map of Timor Tengah Selatan Regency which contains languages, dialects, sub-dialects, and variants. (2) then it was found diachronically related by linguistic means to be produced in diachronic relationships by the linguistic system. (3) there were three variants in this study, namely the Dawan R variant, the Dawan L variant, and the Tetun variant. (4) The study produced a map of the dialectic spiderweb of the TTS Regency.